Program Kampanye Lingkungan River Cleanup Indonesia di Kota Bandung - Ananda Farah Diba; Yadi Supriadi (Bandung Conference Series: Public Relations, 2024)
Abstract. Environmental cleanliness has always been one of the few things that need attention and treated by the society, not only to preserve their beauty, but also to prevent unwanted disasters. The City of Bandung was still plagued by environment disasters such as flood, caused by none other than man himself. River Cleanup Indonesia as one of the non-profit organizations that focus it’s mission on keeping the environment clean especially the river environment, by involving people and technology in the implementation of it’s campaign program. In this research, researches decided to focus the research about the planning design or pattern of the environment campaign program that are held by River Cleanup Indonesia with implementing qualitative research methods and taking case studies to do approaching ways that researches see a unique habit in the planning design or pattern of the environment campaign program. One of the theories about campaign proposed by Rogers and Storey as well as the campaign model proposed by Ostegaard helps researches to understand how River Cleanup Indonesia designed it’s environment campaign program. The purpose of this research was to develop a new perspective in designing a campaign program as a non-profit organization. In obtaining data from doing interviews, observation and documentation researches do analyze the data by the triangulation source of data methods (data reduction, data presentation, deduction, and data verification). Finally researches managed to get answers from doing the research, it can be seen that River Cleanup Indonesia designed an environmental campaign program by directly involving stakeholders and implementing it into a routine every month by implementing a campaign program with the principles of collaboration and inclusiveness. Abstrak. Kebersihan lingkungan selalu menjadi salah satu hal yang perlu diperhatikan serta dijaga oleh masyarakat, tidak hanya untuk melestarikan keindahannya, dan juga dijaga dari terjadinya bencana yang tidak diinginkan. Kota Bandung masih dilanda timbulnya bencana banjir, yang tak lain disebabkan oleh ulah manusia sendiri. River Cleanup Indonesia hadir sebagai salah satu organisasi non-profit yang memfokuskan tujuannya dalam menjaga kebersihan lingkungan terutama lingkungan sungai, dengan melibatkan masyarakat serta teknologi dalam pelaksanaan program kampanye lingkungannya. Dalam penelitian ini, peneliti memutuskan untuk melakukan sebuah penelitian terhadap program kampanye lingkungan yang diselenggarakan oleh River Cleanup Indonesia dengan menerapkan metode penelitian kualitatif serta menerapkan pendekatan studi kasus dimana peneliti melihat adanya keunikan dalam program kampanye lingkungan tersebut. Salah satu teori mengenai kampanye yang dikemukakan oleh Rogers and Storey dan juga model kampanye yang dikemukakan oleh Ostegaard, membantu peneliti dalam memahami program kampanye lingkungan River Cleanup Indonesia. Tujuan dari dilakukannya penelitian ini yaitu untuk mengembangkan sebuah perspektif baru dalam merancang sebuah program kampanye sebagai organisasi non-profit. Dalam memperoleh data dari dilakukannya wawancara, observasi dan dokumentasi peneliti melakukan analisis data dengan metode Triangulasi Sumber Data (reduksi data, penyajian data, penarikan kesimpulan dan verifikasi data). Peneliti berhasil memperoleh jawaban dari dilakukannya penelitian dapat diketahui bahwa River Cleanup Indonesia memiliki program kampanye lingkungan dengan melibatkan stakeholders secara langsung dan menerapkannya menjadi sebuah rutinitas di setiap bualnnya dengan menerapkan program kampanye dengan prinsip kolaborasi serta inklusif.